EXPLORING ERRORS IN ENGLISH DESCRIPTIVE WRITING OF SENIOR HIGH SCHOOL STUDENTS: AN ERROR ANALYSIS STUDY AT SMKN 1 LIMBOTO, GORONTALO - Marwah Mokodompis; Enni Akhmad; Nur Wahidah Tayib Pido (English Education Department, 2026)
This study investigates types and sources of errors in English descriptive writing among tenth-grade students at SMKN 1 Limboto, Gorontalo. Employing a descriptive qualitative approach with Surface Strategy Taxonomy (Dulay, Burt & Krashen, 1982) as the analytical framework, twenty students' descriptive texts were collected and analyzed through Corder's (1967) five-step error analysis procedure. Findings reveal that omission and misformation were the dominant error types, accounting for the highest proportion of total errors. Omission errors primarily involved the copula 'be' and articles, while misformation errors featured incorrect verb forms and inappropriate lexical choices. These errors were predominantly caused by Bahasa Indonesia (L1) interference, intralingual overgeneralization, and limited writing practice opportunities. The study concludes that targeted grammar instruction particularly on copula 'be,' the English article system, and simple present tense morphology and systematic error-correction feedback are essential for improving EFL descriptive writing competence at the vocational high school level.